1990
DOI: 10.1177/154193129003400411
|View full text |Cite
|
Sign up to set email alerts
|

Streamlining the Design Process: Running Fewer Subjects

Abstract: Recent attention has been focused on making user interface design less costly and more easily incorporated into the product development life cycle. This paper reports an experiment conducted to determine the minimum number of subjects required for a usability test. It replicates work done by Jakob Nielsen and extends it by incorporating problem importance into the curves relating the number of subjects used in an evaluation to the number of usability problems revealed. The basic findings are that (1) with betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 3 publications
3
47
0
1
Order By: Relevance
“…Nielsen (1993Nielsen ( , 1994; Lewis (1994) and Virzi (1990Virzi ( , 1992 argue that five or fewer subjects are sufficient to identify most of the usability problems found in a system. Virzi (1990Virzi ( , 1992 showed that this could account for around 80% of the problems. However, other studies recommended using more subjects.…”
Section: Recruitment Of Subjectsmentioning
confidence: 99%
“…Nielsen (1993Nielsen ( , 1994; Lewis (1994) and Virzi (1990Virzi ( , 1992 argue that five or fewer subjects are sufficient to identify most of the usability problems found in a system. Virzi (1990Virzi ( , 1992 showed that this could account for around 80% of the problems. However, other studies recommended using more subjects.…”
Section: Recruitment Of Subjectsmentioning
confidence: 99%
“…The first studies in this area mostly focused on determining the cost-benefit of web interface analysis by estimating the return on investment to justify the cost of usability assessment [24]. In line with this aim, researchers in the 1990s proposed a specific rule of thumb arising from the results of Virzi [23,25] and Nielsen [26][27][28][29]. This rule, known as the five-user assumption, proposes a one-size-fits-all solution in which five users are considered enough for reliable usability testing.…”
Section: Usability Testing Of Medical Devices: Estimating the Sample mentioning
confidence: 99%
“…The estimation of the final number of users for an evaluation sample can be calculated by inserting the p-value into the following well-known error distribution formula [22,23,25,29,31]:…”
Section: Usability Testing Of Medical Devices: Estimating the Sample mentioning
confidence: 99%
“…According to [17], [31], it is possible, with 4 or 5 participants, to detect nearly 80 to 85% of the utilisability problems. Hence, for this first evaluation of the IAS in laboratory, the population is made up of five subjects.…”
Section: Population Implied In the Evaluationmentioning
confidence: 99%